DFT Studies of the Molecluar Structure and Conformational Process of Tricyclic Antidepressants - HAGHDADI, MINA (Asian Journal of Chemistry, 2010)
Trimipramine, imipramine, amitriptyline, desipramine and doxepine were subjected to ab initio (HF/6-31G(d)) and DFT ((b3lyp/6-31G(d) and (b3lyp/6-311+G(d)) computation. Molecular geometries and the activation energies for ring inversions were determined with full geometry optimizations. Results obtained reveals that the changes of side-chain conformation, the angle value between two phenyl rings and the type of N-amine on side-chain can be affected on drug activity.